(untitled) - Del Toro, Vincent (New York, 1965)
This book introduction electric circuit theory, control systems and computers, electromechanical energy conversion
Keywords: Feedback control systems,Computers,Hệ thống điều khiển phản hồi,Máy tính; Mathematical models,Mô hình toán học